REPRESENTASI KOMODIFIKASI AGAMA PADA IKLAN WEBSERIES MIRACLE OF HIJRAH OLEH PRIMALAND - Hafidhoh Ma'rufah (Journal of Islamic Studies and Humanities, 2023)
Developments in technology and information bring changes to the pattern of product marketing. Marketing advertisements undergo various transformations, from print advertisements to ads in the form of videos, from short videos to videos in the form of web series. In its development, too, sharia-based products are increasingly familiar to the public. One form of Sharia product is Sharia-based housing. This residence offers religious facilities such as a prayer room and an archery field. In addition, Sharia housing also uses non-usury payments using an in-house scheme. It is undeniable that the commodification of religion accompanies the advertisements being promoted. Through residential advertisements in the form of web series, Primaland markets its various Sharia residential products. Various commodifications of faith are found in this advertisement. Three forms of commodification were found: Islamic iconography (description of identity), the use of figures with Muslim influencer backgrounds, and the existence of advertising texts or religious messages conveyed through dialogues in web series.